Spatial concentration of Western Poland districts in function of sustainable development level and institutional infrastructure - Malinowski, Mariusz (Economics of the 21st Century, 2018)
This paper attempts to identify the spatial relationships between synthetic measures of sustainable development and synthetic measures of institutional infrastructure development levels in Western Poland districts. The territorial scope of this study covered 112 districts in five voivodeships: Dolnośląskie, Lubuskie, Opolskie, Wielkopolskie and Zachodniopomorskie. The timeframes for this study are limited to one year (2015). Because of the multidimensionality of categories covered by the analysis, this study used TOPSISbased taxonomic measures. In order to determine the strength of spatial relationships between the districts in terms of the subject matter of this study, the analysis of spatial autocorrelation (based on the developed proprietary measures of sustainable development and of the institutional infrastructure development levels) was performed with the use of the global and local Moran’s I statistics
Ekonomia XXI Wieku = Economics of the 21st Century, 2018, Nr 1 (17), s. 22-40
Keywords: sustainable development; institutional infrastructure; spatial relationships; rozwój zrównoważony; infrastruktura instytucjonalna; zależności przestrzenne